Nitric oxide in neurodegeneration: potential benefits of non-steroidal anti-inflammatories - Doherty, Gayle Helane (Neurosci Bull, 2011)
The cellular messenger nitric oxide (NO) has been linked to neurodegenerative disorders due to the increased expression of the enzymes that catalyze its synthesis in postmortem tissues derived from sufferers of these diseases. Nitrated proteins have also been detected in these samples, revealing that NO is biologically active in regions damaged during neurodegeneration. Modulation of NO levels has been reported not only in the neurons of the central nervous system, but also in the glial cells (microglia and astroglia) activated during the neuroinflammatory response. Neuroinflammation has been found in some neurodegenerative conditions, and inhibition of these neuroinflammatory signals has been shown to delay the progress of such disorders. Thus NO and the pathways triggering its release are emerging as an important research focus in the search for strategies to prevent, halt or cure neurodegenerative diseases.